Creating a culture of reflective practice : the role of pedagogical leadership in early childhood - Coughlin, Anne Marie, 1964-; Baird, Lorrie (Redleaf Press, 2022)
"Early childhood professionals and leaders need to reconcile the responsibility between never-ending administrative tasks, ensuring program quality and supporting the growth of others. Creating a Culture of Reflective Practice is a comprehensive practical look at creating systems, structures and protocols for supporting people in large and small organizations, individuals working as mentors, coaches or pedagogical leaders to invite educators into a thinking and learning process about their work"--